Vanilla handbook - Bianchessi, Piero (CTA / Venui Vanilla Company, 2012)
Conceived as a simple text with a large number of self-explanatory illustrations, The Vanilla Handbook provides an excellent, easy-to-follow guide for farmers starting out in the industry and in regions where vanilla is not already well established as a crop.